The Legal Regulation of Sadomasochism and the So-Called “Rough Sex Defence” - Craig, Elaine (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2021)
The focus of this article is on the judicial application of Canada’s sexual assault doctrine in the context of the so called ‘rough sex defence’. Canadian criminal courts have seen an increased prevalence of legal narratives about S/M in recent years. In particular, courts are increasingly confronted with individuals who defend themselves against allegations of sexual assault by claiming that the impugned acts constituted consensual S/M or ‘rough sex’.  The analysis is aimed at illustrating the way in which courts may fail to properly apply legal doctrine because of a problematic approach to the S/M context in which allegations arose.